Growth Mindset in Educational Psychology: Between Conceptual Promise and Pedagogical Misuse - Marini Abd Razak; Hamidah Mohamad (Buletin Edukasi Indonesia, 2026)
Growth mindset has been widely embraced in educational psychology as a construct that promotes motivation, resilience, and academic persistence. However, its rapid diffusion into educational practice has been accompanied by conceptual dilution and pedagogical misuse. This opinion article critically examines the contemporary deployment of growth mindset in educational settings, arguing that it has increasingly been reduced to a motivational slogan detached from instructional quality, assessment systems, and institutional responsibility. Drawing on educational psychology and learning sciences literature, the article problematizes individualistic and decontextualized interpretations of growth mindset and highlights the risks of moralizing effort while obscuring structural inequities. Rather than rejecting the construct, this paper calls for a critical re-engagement with growth mindset as a theoretically grounded, context-sensitive, and pedagogically accountable framework. The article contributes to ongoing debates in educational psychology by questioning prevailing assumptions and urging a more rigorous conceptualization of growth mindset in research and practice.